(untitled) (General Practice, 2024)
Introduction: Regular ultrasonographic check-ups help in early detection and follow-up of different diseases. Ultrasonography (US) is of the utmost diagnostic importance for mammographically „dense breasts“, where glandular tissue is predominant, while in so-called „fat breasts“ it is less reliable. It is used to determine the solid or cystic nature of a lesion, often tissue characterization, and the Doppler technique could reveal vascularization characteristics of the mass. Fibroadenomas are the most common benign breast tumors in women of all ages until menopause, with the highest incidence between 15 and 25 years of age. The US detects distinctly circumscribed, rarely round or lobular, hypoechoic masses with smooth and flat contours, uniform echoes with posterior augmentation, and marginal echo fading. Case report: We presented a female patient aged 21, who had multiple lesions in both breasts (25 lesions in total). Ultrasonographic exams were performed multiple times, in the last 5 years, and magnetic resonance (NMR) was done twice. Histopathologic verification diagnosed fibroadenomas. The biggest masses were surgically removed four times in this patient. What are the next steps? Are surgical interventions needed again, and if not how should she be followed up in the future? Is the implant insertion eligible for the sake of esthetic correction? Conclusion: Ultrasonography is a very significant and important method of follow-up of breast lesions. Mammography and magnetic resonance are used as complementary methods. According to a radiologist’s expert opinions on breast diseases, ultrasonographic exams every six months and NMR may indicate the need for surgical intervention, especially if new